Temporal trend of AIDS in the state of Bahia, Brazil (Research, Society and Development, 2025)
Introduction: Acquired Immunodeficiency Syndrome (AIDS) has a high mortality potential. Temporal analysis of cases is essential to monitor the progress of interventions. Objective: To analyze the temporal trend of aids in Bahia from 2013 to 2023. Materials and Methods: Ecological, descriptive, retrospective study. It analyzed 21,710 aids notifications in the SINAN database. The incidence coefficient and the annual percentage variation (APV) were calculated. A simple descriptive analysis of the variables race/color, education and exposure category was performed, as well as the analysis of the sex ratio and reported deaths. Results and discussion: The incidence rate remained stable until 2019, with slight declines until that period and growth from 2021 onwards. A higher proportion of cases was identified in males, blacks (black and brown), and those with incomplete elementary education in MSM sexual practice. Women showed a significant decline in incidence. Conclusion: During the COVID-19 pandemic, there was a reduction in incidence and an increase in the number of deaths. From 2020 onwards, the rates began to return to pre-pandemic levels. There is a need to implement public policies that address the epidemiological changes that have occurred and that promote better health conditions for the most vulnerable population identified.